Whither justice? An analysis of climate change responses from South East Queensland, Australia - MacCallum, Diana; Byrne, J.; Steele, W. (Pion, 2014)
Climate change is a highly contested policy issue in Australia, generating fierce debate at every level of governance. In this paper we explore a crucial tension in both the policy and the public debate: a seeming lack of attention to social inclusion and broader equity implications. We pay special attention to the municipal scale, where concerns about social difference and democratic participation are often foregrounded in political discourse, using South East Queensland—a recognised climate change ‘hotspot’—as a case study. Mobilising critical discourse analysis techniques, we interrogate three local government climate change response strategies, and place these in the context of transscalar discourse networks which appear to sustain a technocratic, ‘ecological modernisation’ approach to the issue. Finally, we suggest a broad strategy for reimagining this approach to embed a notion of climate justice in our policy thinking about climate change.